Drug prices and pressure group activities in the German health care market: An application of the Becker model - Anne Maria Busch (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2015)
This article analyzes the shifts of power relation and influence between pharmaceutical industry (producers), pharmacies, and social health insurers (SHI) in Germany based on drug prices. Since the health care reform of 2004, these interest groups have negotiated fees and discounts among each other without any intervention from the government. These negotiations and resulting amendments to the original law express the shift of power of the involved groups, which can be explained with the Becker (1983) model. As a result, a trend becomes apparent, which shows a slight increase in political pressure on the part of SHI and a big decrease of political pressure on the part of pharmacies and producers. This reflects the cost control trend in combination with the empowerment incentives for SHI. The last years have shown increased competition between the interest groups, resulting in more balanced power relations. Nevertheless, the most powerful group is still the producer group and the influence of SHI is still very low.
Keywords: D78; I39; D72; I18; 330; interest groups; political pressure; health care market; regulation